Separation of oxidant-initiated and redox-regulated steps in the NF-kappa B signal transduction pathway. - Anderson, M T (1994)
Studies presented here show that overall NF-kappa B signal transduction begins with a parallel series of stimuli-specific pathways through which cytokines (tumor necrosis factor alpha), oxidants (hydrogen peroxide and mitomycin C), and phorbol ester (phorbol 12-myristate 13-acetate) individually initiate signaling. These initial pathways culminate in a common pathway through which all of the stimulating agents ultimately signal NF-kappa B activation. We distinguish the stimuli-specific pathways by showing that the oxidative stimuli trigger NF-kappa B activation in only one of two human T-cell lines (Wurzburg but not Jurkat), whereas tumor necrosis factor alpha and phorbol 12-myristate 13-acetate readily stimulate in both lines. We propose the common pathway as the simplest way of accounting for the common requirements and properties of the signaling pathway. We include a redox-regulatory mechanism(s) in this common pathway to account for the previously demonstrated redox regulation of NF-kappa B activation in Jurkat cells (in which oxidants don't activate NF-kappa B); we put tyrosine phosphorylation in the common pathway by showing that kinase activity (inhibitable by herbimycin A and tyrphostin 47) is required for NF-kappa B activation by all stimuli tested in both cell lines. Since internal sites of oxidant production have been shown to play a key role in the cytokine-stimulated activation of NF-kappa B, and since tyrosine kinase and phosphatase activities are known to be altered by oxidants, these findings suggest that intracellular redox status controls NF-kappa B activation by regulating tyrosine phosphorylation event(s) within the common step of the NF-kappa B signal transduction pathway.